Interpretation of the “Refugee” Term in the International Legal Acts and Laws of the CIS Countries - Borisov, Gennadij A.; Safronova, Elena V.; Sinenko, Vladimir V.; Tonkov, Evgenij E.; Turanin, Vladislav Yu. (Journal of History Culture and Art Research, 2017)
The article describes peculiarities of the "refugee" term interpretation in the international legal acts and laws of the CIS countries. In particular, much attention is paid to its usage in the UN Convention of 1951 “About the status of refugees” and Protocol to it of 1967, and also in the Laws of the Russian Federation (Federal Law of 19.02 1993 No 4528-I “About refugees”), Armenia (The Law of the Armenia Republic of 16.01.2007 No ЗР-47 “About refugees and asylum”), Belarus (The Law of the Belarus Republic of 23.06 2008 No 354-З “About granting to citizens and people with no citizenship a refugee status, additional or temporal protection in the Belarus Republic”) and Ukraine (The Law of Ukraine of 08.07.2011 No 3671-VI “About refugees and people who need additional or temporal protection”). Specific features of the interpretation of the concept of "refugee" in the legal system of these states are defined. The article gives arguments as for a single approach to the “refugee” term interpretation that must be legally confirmed within every country by a traditional international definition.